In the Era of Shared Decision Making, How Would An Iranian Urologist Screen Himself For Prostate Cancer? - Ali Asgari, Majid; Soleimani, Mohammad; Dadkhah, Farid; Lashay, Alireza; Amini, Erfan; Baikpour, Maryam; Amraei, Razie (Urology Journal, 2015)
Purpose: Prostate cancer (PCa) poses a significant health problem in developed countries. Prostate specific antigen (PSA) based screening for PCa is controversial and large trials have failed to show a significant reduction in prostate-specific mortality and all-cause mortality. Considering the contradictory data on PCa screening, current guidelines emphasize shared decision making. Physicians are the ones in charge of helping patients with informed decision making, so we conducted this study to find out what urologists would do for themselves as patients. Materials and Methods: Urologists attending the 15th congress of Iranian Urological Association were invited to participate in a questionnaire-based survey on PCa screening. A total of 184 physicians completed the questionnaire. Results: Of participants 76.8% declared that they would like to be screened. 69.3% of those in favor of screening did not consider digital rectal examination (DRE) as part of their screening program. 62.8% of the urologists willing to be screened chose serial PSA as their follow up method in case their PSA level came above normal ranges, and 35.8% preferred to be biopsied. Conclusion: Urologists tend to prefer PSA screening despite the current controversy about its usefulness. Most of the urologists practicing in Iran do not choose DRE as part of their screening program. Large high quality studies conducted in other countries are needed to look into urologist’s attitudes towards PCa screening, and to investigate their preferences in order to understand the rationale behind their decisions.